CONSTRAINTS ON THE COMPOSITION OF THE CONTINENTAL LITHOSPHERIC MANTLE - McDonough W.F. (My University, 1990)
Major and trace element data for 375 spinel lherzolite and harzburgite xenoliths from continental basalts are used to constrain the nature and composition of the continental lithospheric mantle (CLM). The major and compatible trace elements (e.g., Ni, Co) have similar average and median values, whereas median values of the highly incompatible trace elements (e.g., LREE, Rb) are systematically lower than their average values. Both the average and median compositions have LREE-enriched patterns, with La abundances at about 10 and 3 times C1 chondrites, respectively, and a relatively flat HREE pattern at about 2 times C1 chondrites. Relative to the primitive mantle, highly incompatible trace elements are enriched in the average and median, whereas the mildly incompatible elements (e.g., the middle and heavy REE, Hf, Ti, V, Sc, Al, Ca, etc.) are depleted. The enrichment pattern of incompatible elements in these peridotites is comparable to that in ocean island basalts, although at lower absolute abundances. For most elements the average composition provides an estimate of the bulk composition of the CLM, however for those elements with a strong degree of skewedness in their data the median composition may provide a more reasonable estimate.